(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the diagnostic performance of Xpert MTB/RIF Ultra for tuberculous meningitis in cerebrospinal fluids samples. Methodology: This is a retrospective quantitative cross-sectional study developed from information obtained from the records of the Mycobacteria section of the Laboratório Estadual de Saúde Pública Dr. Giovanni Cysneiros – LACEN-GO from November 2019 to January 2021. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) and their respective 95% confidence intervals were calculated. Results: A total of 247 cerebrospinal fluid samples were included in the study during the period analyzed, with Mycobacterium tuberculosis Complex (MTC) growing in solid culture in two (0.8%) samples and Xpert MTB/RIF Ultra detected 11 (4.5%) samples with genetic material and, according to the technique, the results obtained were classified into: trace (n= 6), very low (n= 1) and low (n= 4). When evaluating the performance of Xpert, the sensitivity was 100% (95% CI 16-100), 96% specificity (95% CI 93-98), 18% PPV (95% CI 18-30) and 100% NPV (CI 95% 100-100). Conclusion: Xpert MTB/RIF Ultra had a high sensitivity and specificity for the diagnosis of tuberculous meningitis, although the latter was been slightly reduced. These results demonstrate that Xpert MTB/RIF Ultra presents improvements that significantly contribute to the identification of cases of tuberculous meningitis.